On the private and social desirability of mixed bundling in complementary markets with cost savings - Christine Halmenschlager; Andrea Mantovani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
The aim of this paper is to study both the private and the social desirability of a mixed bundling strategy that generates a cost savings effect. We confirm that mixed bundling is the dominant strategy for multiproduct firms, although it may give rise to a prisoner's dilemma. Moreover, we show that mixed bundling may maximise social welfare, provided that cost savings are sufficiently high. Finally, we highlight the parametric regions where the social and the private interests coincide, and those where they do not. The recent evolution of broadband telecommunications services provides an ideal framework to apply our theoretical predictions.
Keywords: D43; L13; L41; 330